KESEJAHTERAAN KELUARGA PETANI KAYU MANIS - Elmanora, Elmanora; Muflikhati, Istiqlaliyah; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This research focused on analysis of the correlation of family welfare using three indicators of welfare and the influence of family characteristics toward family welfare of cinnamon farmer families at Tamiai, Kerinci, Jambi. This research involved 50 families that were selected randomly from families in the study side. Families involved in this research were chosen from families of cinnamon farmer in study site who had school-aged children (fourth, fifth, and sixth grade in elementary school). Data collected by interview with questionnaire. Family welfare was indicated by using three indicators those were BPS, BKKBN, and a simple poverty scorecard for Indonesia. Data was analyzed by descriptive, correlation, and regression analysis. The results showed that the families had low welfare based on the third indicators. Family welfare based on scorecard indicator had correlation significantly with family welfare based on BPS and BKKBN indicator. Family welfare was influenced by family size (BPS and BKKBN indicator), father’s age (BKKBN indicator) and family income (BPS, BKKBN, and Scorecard indicator).